Health economic evaluation: cost-effective strategies in humanitarian and disaster relief medicine. Issue 6 (3rd February 2022) - Stewart, Thomas; Bird, P
Abstract : The health economic evaluation is a tool used in disaster relief medicine to generate a cost–benefit analysis. Like all areas of healthcare, disaster relief operations must use finite financial resources, much of which comes from charitable donations and foreign aid. Interventions can be assessed using cost-effectiveness tools and equity assessments. Through these tools, interventions that maximise benefit for a given cost are highlighted in the immediate rapid response phase where food, clean water and shelter are prioritised, often with military support. Beyond this, applications of technology and pre-response training are discussed as cost-effective investments made in anticipation of a disaster. In particular, novel technology-based approaches are being explored to deliver medical advice remotely through telemedicine and remote consulting. This strategy allows medical specialists to operate remotely without the logistical and financial challenges of forward basing at the disaster site. Interventions in disaster relief medicine are often expensive. A specific and regularly reviewed health economic assessment ensures that healthcare interventions yield a maximal impact while limiting waste and working within the budgetary constraints of a disaster medicine response. This is a paper commissioned as part of the humanitarian and disaster relief operations special issue of BMJ Military Health.